2018
DOI: 10.1002/jum.14595
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Fallopian Tube Torsion: A Unique Ultrasound Identity or a Serial Copycat?

Abstract: The US diagnosis of isolated fallopian tube torsion is challenging. A high index of suspicion is necessary to improve its detection, especially when there are possible US signs of torsion in the presence of a normal-appearing ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…A sonographic whirlpool sign, which is used to describe the finding of a small heterogeneous mass with a concentric ring that is provoked by rocking movement of the probe over the mass, might be the most specific sign for fallopian tube torsion 5 8 9. In the study of Raban et al , the whirlpool sign was reported in six patients, of whom two had an accurate diagnosis of isolated fallopian tube torsion 6. Unfortunately, in our presented case, evaluation of the whirlpool sign was not performed.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A sonographic whirlpool sign, which is used to describe the finding of a small heterogeneous mass with a concentric ring that is provoked by rocking movement of the probe over the mass, might be the most specific sign for fallopian tube torsion 5 8 9. In the study of Raban et al , the whirlpool sign was reported in six patients, of whom two had an accurate diagnosis of isolated fallopian tube torsion 6. Unfortunately, in our presented case, evaluation of the whirlpool sign was not performed.…”
Section: Discussionmentioning
confidence: 60%
“…In 29.6%, isolated fallopian tube torsion was correctly diagnosed by ultrasound before surgery. Fallopian tube oedema and the presence of a paraovarian cyst were the most common findings in patients with fallopian tube torsion 6. Even though colour Doppler ultrasound can be useful, the presence of normal flow does not rule out torsion, due to the double vascularisation of the fallopian tube 7.…”
Section: Discussionmentioning
confidence: 99%
“…This sign is not always detectable, especially when a mass is present . A retrospective analysis of 27 cases of IFTT noted that whirlpool sign was noted in only six cases; however, in only 10 of the cases, there was dedicated evaluation for this sign . This study recommended that the sonographic whirlpool sign should be looked for in cases of abnormal adnexal findings and a normal‐appearing ipsilateral ovary when lower abdominal pain was a presenting symptom.…”
Section: Discussionmentioning
confidence: 91%
“…14,15 A retrospective analysis of 27 cases of IFTT noted that whirlpool sign was noted in only six cases; however, in only 10 of the cases, there was dedicated evaluation for this sign. 1 This study recommended that the sonographic whirlpool sign should be looked for in cases of abnormal adnexal findings and a normal-appearing ipsilateral ovary when lower abdominal pain was a presenting symptom. Valsky et al with their retrospective case series of adnexal torsion demonstrated that including as routine, the assessment of the presence of the sonographic whirlpool sign significantly improved the true positive predictive value of this diagnosis (90.0% vs 55.2%, P < 0.005).…”
Section: Managementmentioning
confidence: 99%
“…Adolescents and young women of reproductive age are the most commonly affected (48)(49)(50). Risk factors include intrinsic factors such as history of PID, hydrosalpinx, tubal ligation, and tubal neoplasm, and extrinsic factors such as adhesions, pelvic vascular congestion, adjacent para-ovarian and ovarian masses, uterine masses, a gravid uterus, and trauma (51,52). Patients often report having recently exercised before presentation (53).…”
Section: Isolated Ft Torsionmentioning
confidence: 99%